EFFECT OF SELF-ACTUALIZATION AND REWARD ON EMPLOYEE ACHIEVEMENT PT. MULTISARANA AGRO LESTARI PEKANBARU - Sri Rahayu; Librina Tria Putri; Muhammad Yusril (Jurnal Riset Manajemen Indonesia, 2023)
This study aims to determine the effect of self-actualization and reward simultaneously and partially on the work performance of employees of PT. Multisarana Agro Lestari Pekanbaru. Job performance can be said to be the result of work in quantity and quality that has been achieved by an employee on the implementation of tasks based on responsibilities and main tasks and functions. The analysis used in this study is multiple linear analysis with a total of 100 respondents. Hypothesis testing is done by using the f test and t test. Based on the research results, it can be concluded that simultaneously and partially self-actualization and reward have an effect on work performance. The closeness of the relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable of 79.60%.